2022
DOI: 10.3389/fmicb.2022.1008409
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization and transcriptomic analysis of a novel polymycovirus in the fungus Talaromyces amestolkiae

Abstract: Talaromyces amestolkiae is an important fungal species owing to its ubiquity in soils, plants, air, and food. In this study, we identified a novel six-segmented polymycovirus, Talaromyces amestolkiae polymycovirus 1 (TaPmV-1). Each of the double-stranded (ds) RNA segments of TaPmV-1 contained a single open reading frame, and the proteins encoded by dsRNA1, dsRNA2, dsRNA3, and dsRNA 5 shared significant amino acid identities of 56, 40, 47, and 43%, respectively, with the corresponding proteins of Aspergillus fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…Substantial sequence identity of the 5′-UTRs of two genomic dsRNAs, possibly involved in virion packaging, is a characteristic feature of partitiviruses and the same is true for TpPV-1 ( Fig. 2 B) ( Teng et al, 2022 ; Nibert et al, 2014 ). The viruses in the family Partitiviridae have been reported to be icosahedral in shape and are non-enveloped (45).…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…Substantial sequence identity of the 5′-UTRs of two genomic dsRNAs, possibly involved in virion packaging, is a characteristic feature of partitiviruses and the same is true for TpPV-1 ( Fig. 2 B) ( Teng et al, 2022 ; Nibert et al, 2014 ). The viruses in the family Partitiviridae have been reported to be icosahedral in shape and are non-enveloped (45).…”
Section: Discussionmentioning
confidence: 77%
“…produce structurally related polyketide-based yellow, orange and red pigments ( de Oliveira et al, 2021 ). TaPmV-1 reduced red pigment production by downregulating gene expression ( Teng et al, 2022 ) while TmPV-1 increased host virulence and caused abnormal gene expression ( Lau et al, 2018 ). A comparison between TpPV-1-infected and -free isogenic lines revealed that TpPV-1 altered morphology in culture, decreased host growth and biomass production, and influenced pigmentation, caused by altered gene expression which requires further investigation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The morphotypical diversity of viruses is an important trait that reflects their origin, taxon, evolution and host in the expanding virosphere considering that their morphotypical peculiarities have been influenced by the environment and the specific nature of the host (1–3). Filamentous virions have been widely observed in positive single-stranded RNA [(+)ssRNA)] virus families, such as Closteroviridae , Potyviridae , Alphaflexiviridae , Betaflexiviridae , and Gammaflexiviridae , as well as in some double-stranded (ds) DNA virus families like Lipothrixviridae , positive single-stranded (+ss) DNA virus families (e.g., Inoviridae ), and negative single-stranded (-ss) RNA virus families (e.g., Filoviridae ).…”
Section: Introductionmentioning
confidence: 99%
“…Known polymycoviruses possess multipartite genomes ranging in size from 7.5 to 12.5 kbp, each containing one or two open reading frames (ORFs) (2, 4). They encode four conserved proteins, including an RNA-dependent RNA polymerase (RdRp), a hypothetical protein of unknown function (containing a conserved N-terminus and a zinc-finger motif), a putative methyltransferase (Met), and a proline-alanine-serine rich protein (PASrp) (2, 3, 7). Interestingly, the members Aspergillus fumigatus tetramycovirus 1 (AfuTmV1) from the human pathogenic fungus and Beauveria bassiana polymycovirus 1 (BbPmV1) from an entomopathogenic fungus seem to form non-conventional virions associated with PASrp in a colloidal form, as observed using atomic force microscopy (AFM) (5, 7); Penicillium digitatum polymycovirus 1 (PdPmV1) from a phytopathogenic fungus infecting citrus showed no detectable virus-like particles (8), while Botryosphaeria dothidea RNA virus 1 (BdRV1; also known Botryosphaeria dothidea polymycovirus 1, BdPmV1) from a phytopathogenic fungus infecting pear was associated with some short bacilliform virus-like particles and likely lacked non-conventional virions (9) and only CcFV1 is believed to have a filamentous capsid (4).…”
Section: Introductionmentioning
confidence: 99%